L-Arginine effectively alleviates doxorubicin-induced cardiac dysfunction by inhibiting myocardial fibrosis - Mo-li Zhu; Rui Hao; Meng-yao Zhao; Pei-yao Liu; Hong-dou Zhang; Peng Li; Ya-ling Yin; Hui-jun Liu; Guang-qiu Ren; Jie Zhang; Jing Yang (Molecular Biology Reports, 2026)

Agricultural-waste-derived magnetically responsive compressively resilient aerogel for efficient oil-water separation and thermal insulation - Yuandong Mo; Xinmi Hong; Mufei Chen; Shuzhen Jiang; Ting Huang; Zhongning Guo (Chemical Engineering Journal, 2026)

Probiotic characterization of Ligilactobacillus murinus ZQL11 isolated from healthy dog feces - Duqiang Gong; Luyao Zhang; Lianhong Hong; Shengjun Mo; Ruihong Hu; Xiaonan Wang; Jiantao Zhang (Veterinary Research Communications, 2026)

Antioxidant Activity of Bioactive Peptides Derived from Ulva prolifera in HaCaT Cells and Zebrafish - Li-Ru Hong; Shuo-Qi Wang; Ting-Ting Wu; Zhi-Ru Chen; Mo Chen; Chun-Er Cai; Pei-Min He; Ya Zhao; Rui Jia (Marine Biotechnology, 2026)

Autocatalytic DNA nanosphere assembly activated by endogenous APE1 for intracellular miR-21 imaging - Liuting Mo; Chunfen Zhang; Rongzheng Yuan; Yan Hong; Chan Yang; Weiying Lin (Analytica Chimica Acta, 2026)

RUNX3 mediates Aflatoxin B1-induced hepatocyte apoptosis through modulation of the hippo signaling pathway - Yunying Mo; Yuanyuan Jiang; Shihan Huang; Aliya Yijiati; Shixiong Zheng; Ye Hong; Xiaoyu Xian; Xingyu Yu; Yuxuan Xiao; Qinzhi Wei; Zhini He (Toxicology, 2026)

Spatial and temporal distributions of sedimentary polycyclic aromatic hydrocarbons at a deep-sea waste dumpsite in the East Sea, Korea: Implications for ocean dumping regulations - Chang-Joon Kim; Hye-Eun Kim; Ki-Young Choi; Hae-San Gu; Jun-Mo Jung; Dokyun Kim; Yeonjung Lee; Youngnam Kim; Seongjin Hong; Kyung-Hoon Shin (Journal of Hazardous Materials, 2026)

A GA-XGBoost qualitative model for short-term rainfall forecasting based on GNSS PWV and meteorological parameters - Xu Yujing; Yu Hong; Zhang Jiajia; Liu Jizhou; Wang Shuaimin; Qiu Jiale; Mo Yanhan; Yang Hao (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

DSTs may affect the swimming ability of marine medaka by interfering with the neurotransmitter system and calcium signaling - Zi-min Chen; Mei-qi Li; Jing-xuan Jiang; Yan-hang Mo; Da-wei Li; Hong-ye Li; Wei-dong Yang (Environmental Pollution, 2026)

Lunar water cycle and D/H fractionation driven by solar wind implantation and micrometeorite impacts - Chuanjiao Zhou; Hong Tang; Xiongyao Li; Bing Mo; Wen Yu; Dan Zhu; Yuanyun Wen; Jianzhong Liu (Earth and Planetary Science Letters, 2026)

Stable dry-processed perovskite emitters enabled by eutectic-assisted silica scaffold formation - Jiwoo Hong; Jun-Woo Lee; Ik-Soo Kim; Kyungmoon Kang; Sang-Mo Koo; Himchan Cho; Sang-Wook Kim; Jong-Min Oh; Sunghoon Kim (Chemical Engineering Journal, 2026)

Real-time monitoring and dynamic characterization of crystallization and granulation in HMX systems - Ping Guo; Hong-bin Liu; Hua-mo Yin; Ming-xu Su (Chemical Engineering Journal, 2026)

Benzophenone-type UV filters in aquatic ecosystems: Sources, toxicological impacts, and interactions with coexisting stressors - Yu Ri Jin; Mi-Song Hong; Jin-Sol Lee; Jiezhang Mo; Piotr Maszczyk; Menghong Hu; Youji Wang; Zhou Yang; Minghua Wang; Da-Zhi Wang; Min-Chul Lee; Jae-Seong Lee (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Low enthalpy 3D evaporators coupled with auxiliary thermal management for rapid solar evaporation - Ze-Ming Huang; Hong-Yu Chu; Ye-Tong Liu; Xiang-Jing Mo; Jing Li; Chong-Chen Wang; Peng Wang; Xiao-Hong Yi (Chemical Engineering Journal, 2026)

Phyconomic and product safety–related advantages of callus-derived Kappaphycus striatus across five successive vegetative propagation cycles under field farming conditions in Van Phong Bay, Vietnam - Vu Thi Mo; Le Trong Nghia; Phan Minh-Thu; Pham Hong Ngoc; Pham Duc Thinh; Huynh Hoang Nhu Khanh; Tran Mai Duc; Cao Van Nguyen; Huynh Minh Sang; Hua Thai An (Journal of Applied Phycology, 2026)

Assessing recent anthropogenic carbon dioxide and acidification in the Ross Sea, Antarctica - Ahra Mo; Tae-Wook Kim; Jinyoung Jung; Tae-Wan Kim; Jung-Ok Choi; Yewon Kim; Hyoung Sul La; Jisoo Park; Kyeong-Hong Kim; Keyhong Park (Marine Environmental Research, 2026)

Tuning the thermal reactivity of low-rank coal: The structural role of phenolic hydroxyl groups from molecular aggregation to pore collapse - Hao Xu; Jin-Xi Wu; Yu-Hong Kang; Xing Fan; Ya-Ya Ma; Guang-Hui Liu; Ran-Ran Hou; Zhong-Qiu Liu; Wen-Long Mo; Yao Lu (Fuel, 2026)

Long-term protective efficacy and distinct immune responses of live and inactivated vaccines against cryptocaryoniasis in orange-spotted grouper (Epinephelus coioides) - Hai Zhang; Huicheng Wu; Shunli Che; Yuhao Hong; Yanwei Li; Xueming Dan; Zequan Mo (Fish & Shellfish Immunology, 2026)

Physiological Responses and Functional Performance of Eucheumatoid Seaweeds Under Prolonged Low-Salinity Stress - Jianling Zhan; Zhenwei Mo; Fen Cheng; Xianming Tang; Hong Du; Qiong Wu (Journal of Marine Science and Engineering, 2026)
Low-salinity events caused by heavy rainfall and freshwater runoff pose significant environmental constraints on eucheumatoid seaweed mariculture in coastal areas. In this study, five eucheumatoid seaweeds, including three strains of Kappaphycus alvarezii (Hn-R, Hn-G, and Ma-R), Kappaphycus striatum, and Eucheuma denticulatum, were exposed to 22, 26, and 30 psu for 36 days. Growth performance, photosynthetic pigments, chlorophyll fluorescence parameters, oxidative damage, and antioxidant responses were determined. To compare the actual physiological performance of different seaweeds under each salinity condition, a functional performance score was calculated using membership function analysis based on relative growth rate, chlorophyll a, carotenoids, photosynthesis, and malondialdehyde. Low salinity generally reduced growth, photosynthetic pigment content, and photosystem II performance, while increasing malondialdehyde content and antioxidant-related parameters, indicating that prolonged low-salinity exposure induced both physiological inhibition and oxidative stress responses. At 22 psu, K. alvarezii Ma-R showed the strongest functional performance, followed by K. striatum and E. denticulatum. At 26 psu, E. denticulatum showed the strongest functional performance, followed by K. alvarezii Ma-R and K. striatum. These results indicate that eucheumatoid seaweeds differ in their functional performance under mild and more severe low-salinity tolerance, providing physiological evidence for selecting candidate eucheumatoid seaweeds for salinity-fluctuating coastal mariculture.

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

High-density lipoprotein antioxidant function is associated with lipid profiles and lipid-lowering therapy - Hong-Yu Cao; Zhi-Wei Mo; Zhen-Sheng Ma; Yi-Fang Liu; Chen Wang; Yue-Ming Peng; Yue-Ting Kang; Yan Li; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Sediment facies regulate organic and shell-derived carbonate carbon storage in the Shinan tidal flats, Korea - Yoon-Seo Kim; Yeo-Bin Park; Ji-Won Park; Eui-Joo Kim; Sang-Pil Lee; Seung-Jun Lee; Do-Hun Ryu; Ji-Su Ko; Jun-Mo Kim; Jae-Hoon Park; Yong-Sik Hong; Sang-Kyoung Lee; et al. (Regional Studies in Marine Science, 2026)

A novel PGPR Streptomyces sp. for efficient phthalate biodegradation: Mechanistic insights and application in contaminated soil - Hong-Jia Huang; Yi-Tong Huang; Miao Xin; Xiao-Qiong Zhu; Hui LYU; Jiayu Hu; Lei Xiang; Yan-Wen Li; Hai-Ming Zhao; Quan-Ying Cai; Meng Li; Da-Wei Li; et al. (Journal of Hazardous Materials, 2026)

A Ca-MOF@COF composite and its in situ grown gel membrane for highly efficient capture of Cd2+ - Xue-Mei Liu; Chuang-Chuang Zhang; Kun Yang; Wei-Liang Jin; Guan-Lian Mo; Rui Liu; Hong-Xin Jiang; Hao-Jie Cui; De-Ming Kong (Journal of Cleaner Production, 2026)

ZnO nanoparticles enhance vernalized rapeseed yield under cadmium stress by boosting photosynthesis and antioxidant response while reducing cadmium accumulation - Zhe Jiang; Xuechan Zhang; Xiangbin Yao; Hong Yang; Wentao Yi; Zhaowen Mo; Xiangru Tang (Plant Cell Reports, 2026)

Relative quantitative data of cosmetics consumption: An online survey in Guangzhou, China - Junfeng Deng; Zhen Wu; Xiaodan Lu; Xiaoyu Xian; Shixiong Zheng; Yunying Mo; Tianyang Liu; Siyu Sun; Shihan Huang; Ye Hong; Xingyu Yu; Aliya Yijiati; et al. (Regulatory Toxicology and Pharmacology, 2026)

Multifunctional bacterial consortium degrading phthalates, promoting plant growth and inhibiting soil-borne pathogenic fungi - Jie-bin Zhou; Qiong-Wen Zhang; Yong-Ling Zhou; Hai-Feng Chen; Yu-Hong Huang; Hai-Ming Zhao; Lei Xiang; Yan-Wen Li; Ce-Hui Mo; Quan-Ying Cai; Qing X. Li (Journal of Hazardous Materials, 2026)

Deep eutectic solvent-based ultrasound extraction of bioactive flavonoids from Coreopsis tinctoria Nutt.: Process optimization, HPLC analysis, and preliminary bioactivity evaluation - Peng Wen-Yu; Lin Fang-Qi; Mo Hong-Bo; Hu Tong-Yi; Ou Hong (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

A comparative study of radiation resistance and exposure history from Chang'e-6 lunar minerals - Haiyan Long; Hong Tang; Tian Zhang; Bing Mo; Chuanjiao Zhou; Yuanyun Wen; Xiongyao Li; Jianzhong Liu (Acta Geochimica, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Silkworm excrement–immobilized bacteria for synergistic remediation of phthalate esters in agricultural soil - Yong-Hong Chen; Huan Du; Ying-Xi Liu; Ke Xu; Jin-Cheng Ye; Bai-Lin Liu; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Hazardous Materials, 2026)

Engineered biosensor-driven food biomanufacturing: Intelligent multi-scale systems for nutrient synthesis monitoring and quality control - Xinya Mo; Wen Zhu; Shutong Zhang; Zhuoning Cao; Qiang Zhao; Hao Dong; Hong Jiang; Jianan Sun; Sai Wang; Xiangzhao Mao (Trends in Food Science & Technology, 2026)

Effective separation of organic species from a shale oil sludge - He-Qi Liu; Xian-Yong Wei; Zhi-Hao Ma; Jing Chen; Xiao-Yan He; Zhi-Min Zong; Xing Fan; Yu-Hong Kang; Fang-Jing Liu; Hai-Xu Zou; Guang-Hui Liu; Yierxiati Dilixiati; et al. (Journal of Environmental Management, 2026)

Enhancing climate resilience of global dryland maize to cope with future 50-year climate warming - Jing Wang; Bao-Zhong Wang; Fei Mo; Yinglong Chen; Mohammad Ashraf; Yang Wang; Jian-Ming Li; Hai-Xia Duan; Yajie Song; Levis Kavagi; Hong-Yan Tao; You-Cai Xiong (Global Environmental Change, 2026)

Hybrid square steel tubular columns with PET FRP jacket and inner FRP-concrete core: Axial compression behavior and numerical analysis - Lan Zeng; Xuqi Liang; Ziyong Mo; Hong Yuan (Engineering Structures, 2026)

Reprogramming lipid metabolism and morphology engineering in Yarrowia lipolytica for algae-free, high-titer production of esterified astaxanthin - Mo-Han Zhu; Hong-Ze Zhou; Zhijie Liu; Hong Zhu; Jun Chen; Chen Yang; Feng Liu; Qiang Hua (Chemical Engineering Journal, 2026)

Zero-energy, capillarity-gravity self-filtration system: A sustainable and ultra-low cost solution for high-efficiency microalgae removal - Haochuan Lin; Junjie Yang; Yuqin An; Mo Dong; Zupei Wang; Yiqi Tang; Huanhuan Tang; Hong Yao; Xinyang Li; Wen Zhang (Chemical Engineering Journal, 2026)

Non-additive effects of norethisterone and levonorgestrel mixtures on lipid metabolism at environmentally relevant concentrations - Zeyan Zhang; Kejin Zhou; Yafang Chen; Kun Xie; Mo Zhao; Shimiao Zhao; Zhiqiang Xia; Wenjun Hong; Pan Ma; Xinyi Zhou (Aquatic Toxicology, 2026)

Haplotypes of Chloroquine Resistance Marker Genes Among Uncomplicated Malaria Cases in Lagos, Nigeria - Uche Thecla Igbasi; Wellington Aghoghavia Oyibo; Jun-Hu Chen; Hong Quan; Sunday Aremu Omilabu; Shen-Bo Chen; Hai-Mo Shen; Xiao-Nong Zhou (Biochemical Genetics, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Degassing from Chang’e-6 ilmenite surfaces revealed by a foamy texture: insights for volatile cycles on the Moon - Tian Zhang; Hong Tang; Xiongyao Li; Bing Mo; Yuanyun Wen; Sheng Zhang; Wen Yu; Chuanjiao Zhou; Haiyan Long; Jianzhong Liu (Geochimica et Cosmochimica Acta, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

Overcoming hydroxyl radical quenching in high-salinity wastewater: Electrostatically shielded porous perovskite boosts adsorption-oxidation of organic contaminants - Chao Li; Zaixing Li; Xueqing Xu; Hong Mo; Haitang Wang; Jiaxuan Deng; Shenghuan Liu; Yunzhi Qian; Mengfei Liu; Shilong He; Haijiao Xie (Desalination, 2026)

Facile molten salt synthesis of Co@N-C catalysts enables highly efficient HMF-to-FDCA conversion under mild conditions - Hao-Yue Ma; Jun-Fei Gu; Xing-Chuan Li; Zhan Chen; Qi-Yu Fu; Francis Verpoort; Wen-Jie Mo; Zheng Liu; Cheng Chen; Soon Hyeok Hong; Zongkui Kou (Chemical Engineering Journal, 2026)

Development and application of a new simple algorithm for stochastic modeling of daily ground snow loads: A case study in Northeastern China - Huamei Mo; Yuanyuan Li; H.P. Hong; Guolong Zhang; Qingwen Zhang; Feng Fan (Cold Regions Science and Technology, 2026)

Sources of potentially toxic elements in lake sediments near an abandoned mine: understanding the combination of uranium radioisotopes - Yun-Mo Yang; Seung-Hee Hong; Hyun-Gi Jeong; Min-Hee Chae; Tae-Woo Kang; Won-Seok Lee (Environmental Geochemistry and Health, 2026)

Presence and sources of antibiotics in Dongzhai Harbor, Hainan Island - Tuan-Tuan Wang; Hong-Jin Zhang; Tuan-Qi Guo; Jia-Yu Luo; Bi-Jiao Li; Wen-Qing Liao; Ling Mo; Sai Wang; Yue-Hua Huang (Marine Pollution Bulletin, 2025)

Significant generational effects of tetracyclines upon the promoting plasmid-mediated conjugative transfer between typical wastewater bacteria and its mechanisms - Lingling Rong; Baoyin Zhang; Hongmu Qiu; Hailin Zhang; Jiayin Yu; Qing Yuan; Ligui Wu; Hong Chen; Yuanmin Mo; Xiaoming Zou; Xubiao Luo (Water Research, 2025)

Anti-quenching oxidation by surface charge engineering: MOF-derived anionic perovskite enable efficient saline organic wastewater remediation via free radical protection microzone - Chao Li; Xueqing Xu; Hong Mo; Mengfei Liu; Shilong He (Journal of Water Process Engineering, 2025)

Co-adsorption of heavy metals and antibiotic pollutants by microplastic in aquatic environments and its mechanisms: A review - Yuanmin Mo; Hong Chen; Yujin Li; Binggang Chen; Ligui Wu; Xiaoming Zou (Journal of Environmental Chemical Engineering, 2025)

On snow hazard mapping over the Chinese mainland by using observational and reanalysis datasets - L.F. Jiang; H.M. Mo; H.P. Hong (Cold Regions Science and Technology, 2025)

Age-standardized incidence, prevalence, mortality rates and future projections of autoimmune diseases in China: a systematic analysis based on GBD 2021 - Yanhua Xiao; Xuezhi Hong; Ranjana Neelagar; Hanyou Mo (Immunologic Research, 2025)

Vasicine derivatives as potent MAPK inhibitors for psoriasis treatment - Qing-Yan Mo; Wen-Gang Wang; Xiao-Hong Li; Yun-Hong Shen; Yun Sun; Ze-Wei Mao; Chun-Ping Wan (Molecular Diversity, 2025)

Distribution, sources, and health risks of PM2.5 and PM1-bound polycyclic aromatic hydrocarbons in the Pearl River Delta - Guang-Hong Zhai; Yue Wen; Mo Yang; Qi-Zhen Wu; Wan-Ting He; Li-Xia Liang; Le-Bing Wang; Yun-Ting Zhang; Jing-Wen Huang; Jia-Xin Zhou; Min Li; Gao Meng; et al. (Environmental Monitoring and Assessment, 2025)

Sorafenib induces intestinal toxicity by disturbing gut microbiota and activating the LPS/TLR4/NF-κB signaling pathway in mice - Yaning Xu; Yongshi Mo; Wenxin Zhou; Meirong Qin; Meifang Li; Guo Yin; Hansheng Yu; Yuchun Chen; Haiyan Du; Yibao Jin; Houshuang Huang; Chong Ma; et al. (Toxicology, 2025)

Smartphone-assisted Ce-POM/CuBTC peroxidase-like colorimetric detection of H2O2 and ascorbic acid in food samples - Yiyi Zhang; Haibo Zhang; Chengyuan Ma; Yihang Yang; Xuan Mo; Yuan Shi; Zhijia Yin; Hong Li; Lin Sun (Food Chemistry, 2025)

Regulating the morphological structure of cellulose acetate ultrafiltration membrane by adjusting the ratio of N, N-dimethylacetamide: N-methyl pyrrolidone in co-solvent to enhance separation and anti-fouling performance - Minfu Mo; Yaling Lin; Danni Lin; Xiaojuan Ma; Yubin Hong; Lihui Chen; Dong Wang; Liulian Huang (Desalination, 2025)

Dual-strategy stabilization of zinc anodes through solvation regulation and interfacial engineering in aqueous zinc ion batteries - Weilin Yan; Yifan Wang; Lufan Liu; Feiyu Tao; Yang Huang; Zhaoqian Li; Li'e Mo; Hong Zhang; Linhua Hu (Chemical Engineering Journal, 2025)

Ni/Zr co-doping strategy to promote cyclic performance of CaO-based materials for thermochemical energy storage: Experimental and first-principles insights - Zhu-yu Li; Le-ran Li; Jing-yi Liu; Qi Niu; Zhi-mo Fang; Ji-hong Li; Kai Li; Qiang Lu (Chemical Engineering Journal, 2025)

Albumin mediates the association between maternal exposure to multiple metals and gestational diabetes mellitus: Findings from the Guangxi Birth Cohort Study - Hualong Qiu; Yu Bao; Shengzhu Huang; Yuen Zhong; Caitong He; Long Tian; Yu Zhang; Bangzhu Luo; Tao Liang; Baohong Pang; Mujun Li; Hong Cheng; et al. (Journal of Trace Elements in Medicine and Biology, 2025)

Interpretable machine learning models for predicting hormesis of binary antibiotic mixtures on Vibrio qinghaiensis sp.-Q67 - Ling-Yun Mo; Si-Tong Long; Pei-Pei Zhang; Yan-Peng Liang; Hong-Hu Zeng; Yong-Hong Zhang; Li-Tang Qin (Journal of Hazardous Materials, 2025)

Simplified synthetic community reveals the enrichment of phthalate-degrading bacteria in maize rhizosphere enhancing phthalate degradation - Jia-Lu Wei; Yu-Hong Huang; Jun-Hua Li; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Yan-Wen Li; Ce-Hui Mo; Quan-Ying Cai; Qing X. Li (Journal of Environmental Chemical Engineering, 2025)

Mechano-responsive 3D-printed organic afterglow systems with programmable color output - Ziyi Wang; Yuhan Wang; Wanqi Mo; Longming Jin; Wei Hong (Chemical Engineering Journal, 2025)

An environmentally friendly hydrophobic composite aerogel based on pineapple straw for oil-water separation, thermal insulation and flame retardancy - Yuandong Mo; Xinmi Hong; Ting Huang; Mufei Chen; Zhongning Guo (Chemical Engineering Journal, 2025)

Efficiencies, pathways and mechanism on simultaneous biodegradation of phthalates and polycyclic aromatic hydrocarbons by bacterial consortium - Yao-Si Chen; Jia-Lu Wei; Jie-Bin Zhou; Yu-Hong Huang; Guang-Xuan Tang; Yan-Wen Li; Hai-Ming Zhao; Lei Xiang; Nai-Xian Feng; Ce-Hui Mo; Quan-Ying Cai; Qing X. Li (Journal of Environmental Chemical Engineering, 2025)

Degradation efficiency for phthalates and cooperative mechanism in synthetic bacterial consortium and its bioaugmentation for soil remediation - Huixiong Lü; Yu-Hong Huang; Qi-Fang Li; Hai-Ming Zhao; Lei Xiang; Hui Li; Yan-Wen Li; Ce-Hui Mo; Quan-Ying Cai (Environmental Pollution, 2025)

Lead, cadmium and arsenic species in spices from markets in Hanoi, Vietnam - Phuong Duc Luu; Mo Hong Thi Bui; Tien Duy Doan; Thuy Cam Quan; Thuy Xuan Vu; Mai Thi Dang (Food Additives & Contaminants Part B-Surveillance, 2025)

Influence of oceanic emission and gas transfer velocity on atmospheric dimethyl sulfide distribution over the Southern Ocean - Jaemin Ju; Ahra Mo; Keyhong Park; Miming Zhang; Jinpei Yan; Jinyoung Jung; Louisa Emmons; Joo-Hong Kim; Taewook Park; Jisoo Park (Marine Pollution Bulletin, 2025)

New insights into rhizosphere bacterial community shaped by lettuce genotypes for divergent degradation efficiencies of phthalates - Guang-Xuan Tang; Yu-Hong Huang; Li-Wan Feng; Yu-Chang Hu; Jia-Lu Wei; Huixiong Lü; Li-Hui Liu; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; et al. (Journal of Hazardous Materials, 2025)

The tolerance mechanism of diarrhetic shellfish toxins mediated by the extracellular regulated protein kinase (ERK) pathway in the mussel Perna viridis - Jin-jin Lv; Yu-jie Liu; Yan-hang Mo; Li-yan Deng; Yang Liu; Hong-ye Li; Li Zhang; Wei-dong Yang (Journal of Hazardous Materials, 2025)

A new method for mechanical identification of unstable sliding rock - Yan Du; Hong-da Zhang; Mo-wen Xie; Yu-jing Jiang; Santos Daniel Chicas; Jing-nan Liu (Bulletin of Engineering Geology and the Environment, 2025)

Numerical Investigation of Offshore CCUS in Deep Saline Aquifers Using Multi-Layer Injection Method: A Case Study of the Enping 15-1 Oilfield CO2 Storage Project, China - Jiayi Shen; Futao Mo; Zhongyi Tao; Yi Hong; Bo Gao; Tao Xuan (Journal of Marine Science and Engineering, 2025)
Geological storage of CO2 in offshore deep saline aquifers is widely recognized as an effective strategy for large-scale carbon emission reduction. This study aims to assess the mechanical integrity and storage efficiency of reservoirs using a multi-layer CO2 injection method in the Enping 15-1 Oilfield CO2 storage project which is the China’s first offshore carbon capture, utilization, and storage (CCUS) demonstration. A coupled Hydro–Mechanical (H–M) model is constructed using the TOUGH-FLAC simulator to simulate a 10-year CO2 injection scenario, incorporating six vertically distributed reservoir layers. A sensitivity analysis of 14 key geological and geomechanical parameters is performed to identify the dominant factors influencing injection safety and storage capacity. The results show that a total injection rate of 30 kg/s can be sustained over a 10-year period without exceeding mechanical failure thresholds. Reservoirs 3 and 4 exhibit the greatest lateral CO2 migration distances over the 10-year injection period, indicating that they are the most suitable target layers for CO2 storage. The sensitivity analysis further reveals that the permeability of the reservoirs and the friction angle of the reservoirs and caprocks are the most critical parameters governing injection performance and mechanical stability.

Quantum mechanics-based structural analysis of phenolic glycosides from Cuscuta japonica seeds with protective effects against H2O2-induced oxidative stress in SH-SY5Y cells - Hau Thi Hong Bui; Ajay Uprety; Trung Huy Ngo; Yun-Seo Kil; Punam Thapa; Jongseo Mo; Hyukjae Choi; Soo Young Kim; Joo-Won Nam (Phytochemistry, 2025)

Uptake, translocation, and biotransformation of phthalate acid esters in crop plants: A comprehensive review - Nai-Xian Feng; Bogui Pan; Hong-Jia Huang; Yi-Tong Huang; Hui Lyu; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Da-Wei Li; Ce-Hui Mo (Journal of Hazardous Materials, 2025)

Effects of novel bio-organic fertilizer on the remediation of PAEs-contaminated soil and its bacterial community composition - Hong-Jia Huang; Bogui Pan; Qi-Feng Liang; Wan-Ting Zhang; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Chemical Engineering, 2025)

Deciphering the contribution of algae-rich microbial communities to dissolved organic matter in a eutrophic lake with distinct rainy and dry seasons - Han Yan; Hong-Fa Guo; Jia-Xun Li; Zhuo Chen; Shi-Qi Yin; Mo-Yu Shen; Yi Tao; Yin-Hu Wu; Hong-Ying Hu (Algal Research, 2025)

Emodin ameliorates dopaminergic neuron loss in the MPP + induced parkinson’s disease model: significant inhibition of ferroptosis by activating UQCRC1 protein - Ayiguzhali Yusun; Hong-Mei Wan; Hua-Xian Chen; Mo Sun; Chen-Ning Zhang; Xu-Dong Ding (Natural Product Research, 2025)

Magnetic field-assisted bioleaching of cathode materials from spent Li-ion batteries using Acidithiobacillus ferrooxidans - Jun-Ho Hong; Jeon Kim; Ejin Han; Seon-Mo Yang; Hee-Soo Kim; Jihwan Kim; Chong Seung Yoon (Chemosphere, 2025)

Catalytic hydroconversion of oxydibenzene and benzyloxybenzene over NiCs/Al2O3 - Hong-Hui Gong; Xian-Yong Wei; Wen-Long Mo; Zhi-Min Zong; Guang-Hui Liu; Pei Liu; Kun-Peng Jiao (Fuel, 2025)

Dynamic encryption enabled by circularly polarized carbon dot-based afterglow composites featuring hierarchical tri-mode thermochromic emission - Haozhi Wang; Longming Jin; Wanqi Mo; Wei Hong (Chemical Engineering Journal, 2025)

Cereal-legume intercropping stimulates straw decomposition and promotes soil organic carbon stability - Wei Wang; Meng-Ying Li; Qing-Hui Wen; Yue Ma; Zhi-Ming Zhang; Muhammad Maqsood Ur Rehman; Fei Mo; Hong-Yan Tao; Bao-Luo Ma; Joann K. Whalen; You-Cai Xiong (Science China Life Sciences, 2025)

Experimental and computational study on xylan pyrolysis: The effect of branch structures - Bin Hu; Wen-ming Zhang; Xue-Wen Guo; Ji-hong Li; Xiao Yang; Zhi-mo Fang; Ji Liu; Qiang Lu (Fuel, 2025)

The inventory of OH and H2O in the non-polar regions of the Moon - Wen Yu; Hao Yan; Hong Tang; Xiongyao Li; Yu Wei; Huiming Bao; Chuanjiao Zhou; Bing Mo; Yanxue Wu; Haiyang Luo; Jialong Hao; Ruiying Li; et al. (Earth and Planetary Science Letters, 2025)

Mussel-inspired integrated functional 3D printed scaffolds with molybdenum disulfide nanoflowers for tumor therapy and bone reconstruction - Lan Li; Rongcan Wu; Ruchen Hong; Xiaolong Chen; Tingting Huang; Siyi Huang; Xianglei Mo; Zhiyi Wang; Wenge Liu; Yanjin Lu; Ye Wu; Jinxin Lin (Chemical Engineering Journal, 2025)

Microbial augmented aerobic composting for effective phthalates degradation in activated sludge - Bogui Pan; Hong Tian; Qi-Feng Liang; Hong-Jia Huang; Yi-Tong Huang; Bai-Lin Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Management, 2025)

Evaluation of water vapor from CARRA reanalysis based on GNSS and radiosonde observation in the Arctic - Ce Zhang; Shuaimin Wang; Yuling Zhao; Yujing Xu; Jiajia Zhang; Yanhan Mo; Hong Yu (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

O3–NOx–VOCs photochemical pollutant dispersion in 2D street canyon under effects of solar radiation - Jie Liang; Jian Hang; Shiguo Jia; Jiajia Hua; Bo Zhao; Xuelin Zhang; Hong Ling; Ziwei Mo (Atmospheric Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

An ultrathin Al2O3 ceramic membrane prepared by organic-inorganic blending with solvent evaporation and high-temperature sintering for highly efficient oil/water separation - Yixiao Wang; Zishang Chen; Yuxuan Zhu; Hong Wang; Zhenyu Cui; Xianhui Li; Jiahao Mo; Jianxin Li (Journal of Water Process Engineering, 2025)

Microplastics-exposure experience aggravates the accumulation of diarrhetic shellfish toxins (DSTs) in thick-shell mussel Mytilus coruscus through impairing detoxification processes - Kuan-Kuan Yuan; Ying-Ying Yu; Yu-Jie Liu; Xiu-Lin Yang; Yan-Hang Mo; Wei Shi; Guang-Xu Liu; Hong-Ye Li; Wei-Dong Yang (Journal of Hazardous Materials, 2025)

Presence and sources of per- and polyfluoroalkyl substances (PFASs) in the three major rivers on Hainan Island - Wang-Qing Tang; Tuan-Tuan Wang; Jiang-Wei Miao; Hua-Dong Tan; Hong-Jin Zhang; Tuan-Qi Guo; Zhong-Bing Chen; Chun-Yuan Wu; Ling Mo; Bi-Xian Mai; Sai Wang (Environmental Research, 2025)

Hyaluronic acid-functionalized ruthenium photothermal nanoenzyme for enhancing osteosarcoma chemotherapy: Cascade targeting and bidirectional modulation of drug resistance - Weifeng Chen; Hao Feng; Yinyin Mo; Zhihui Pan; Shichen Ji; Hong Liang; Xing-Can Shen; Bang-Ping Jiang (Carbohydrate Polymers, 2025)

Luminescent iron phthalocyanine organic polymer nanosheets with space-separated dual-active sites for the detection and photocatalytic reduction of Cr(Ⅵ) from wastewater - Wenfei Ding; Zhaoyi Mo; Jia Qi; Mengying Wang; Junyu Zou; Kuo Wang; Daxiang Gong; Yongju Zhao; Hong Miao; Zhongquan Zhao (Environmental Research, 2025)

Isolation, Structure, and Biological Activities of Exopolysaccharides from Actinomycetes: A Review - Xiao-Lian Wei; Song-Yi Mo; Rola Ali-Saeed; Hong Zeng (Current Microbiology, 2025)

Characteristics and sources of potentially toxic elements in road-deposited sediments at the Port of Busan, South Korea: A key contributor to port sediments pollution - Jin Young Choi; Jae Seong Lee; Kyung-Tae Kim; Geun-Ha Park; Jun-Mo Jung; Gi Hoon Hong; Kongtae Ra; Sangmin Hyun; Chang Eon Lee; Eun-Ji Won (Marine Pollution Bulletin, 2024)

Investigating the environmental dynamics of emerging pollutants in response to global climate change: Insights from bibliometrics-based visualization analysis - Bogui Pan; Hong Tian; Boyou Pan; Ting Zhong; Miao Xin; Jinhua Ding; Junyu Wei; Hong-Jia Huang; Jing-Qian Tang; Fengtao Zhang; Nai-Xian Feng; Ce-Hui Mo (Science of The Total Environment, 2024)

Regulation of freshwater filamentous green algae (Cladophora) and its impact on malodorous volatile organic sulfur compound (DMS) by biomanipulation - Yutai Dai; Yu Lin; Ping Deng; Jiping Chen; Weijie Li; Qiang Gao; Hong Shen; Qiutong Peng; Mo Chen; Xuwei Deng (Science of The Total Environment, 2024)

Metal-organic framework-sealed heterogeneous nanoenzyme: A dual-mode core–shell sensor for sensitive determination of the chlorpyrifos residue in environment and bioaccumulation in food - Jintong Liu; Jie Tang; Yanyang Mo; Lin Zhou; Tingting Cai; Hong Yang (Chemical Engineering Journal, 2024)

Optimizing ABA-based chemically induced proximity for enhanced intracellular transcriptional activation and modification response to ABA - Zeng Zhou; Yue-Qi Wang; Xu-Nan Zheng; Xiao-Hong Zhang; Lu-Yao Ji; Jun-You Han; Ze-Cheng Zuo; Wei-Liang Mo; Li Zhang (Science China Life Sciences, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Corrigendum to “Np-Fe0 addition affects the microstructure and composition of the microwave-sintered lunar soil simulant CLRS-2” [Adv. Space Res. 73(1) (2024) 945–957] - Tian Zhang; Hong Tang; Xiongyao Li; Chuanjiao Zhou; Wen Yu; Bing Mo; Jianzhong Liu; Xiaojia Zeng (Advances in Space Research, 2024)

Low temperature alleviated the adverse effects of simulated transport stress on the intestinal health in Chinese soft-shelled turtle Pelodiscus sinensis - Jiaxiang Luo; Jintao Gao; Haoran Song; Zhiyin Mo; Binquan Hong; Leyan Zhu; Wei Song; Guoying Qian; Caiyan Li (Fish & Shellfish Immunology, 2024)

Classification and regression machine learning models for predicting the combined toxicity and interactions of antibiotics and fungicides mixtures - Li-Tang Qin; Jun-Yao Zhang; Qiong-Yuan Nong; Xia-Chang-Li Xu; Hong-Hu Zeng; Yan-Peng Liang; Ling-Yun Mo (Environmental Pollution, 2024)

Integrating DNA logic computation and Self-Replication on nanospheres for amplified detection of Dual miRNAs - Liuting Mo; Yan Hong; Rongzheng Yuan; Mingxiu Mo; Chan Yang; Weiying Lin (Chemical Engineering Journal, 2024)

Acinetobacter corruptisaponis sp. nov., Isolated from a Spoiled Bath Lotion - Ying-Si Wang; Gang Zhou; Hong-Bing Tao; Lei Gao; Bao-Zhu Fang; Xiu-Jiang Yang; Hong Peng; Xia Wen; Xiao-Mo Huang; Jie Wang; Wen-Jun Li; Qing-Shan Shi; et al. (Current Microbiology, 2024)

Microplastics positively mediate soil multifunctionality in dryland - Peng-Yang Wang; Ze-Ying Zhao; Kadambot H.M. Siddique; Xiao-Bin Xiong; Hong-Yan Tao; Yue Ma; Fei Mo; Yinglong Chen; Yajie Song; William R. Burch; Baoluo Ma; Song Wang; et al. (Resources, Conservation and Recycling, 2024)

Passivating perovskite surface defects via bidentate chelation for high-performing solar cells - Mengting Han; Li’e Mo; Zhiqian Yang; Aiqing Sun; Hong Zhang; Bolin Li; Zhaoqian Li; Xianxi Zhang; Rahim Ghadari; Yang Huang; Linhua Hu (Chemical Engineering Journal, 2024)

Highly crosslinked polymeric matrix for efficient ultralong dual-mode afterglow with multiple responses - Yusheng Zhou; Longming Jin; Wanqi Mo; Mingyang Liu; Yuewei Zheng; Wei Hong; Guodong Liang (Chemical Engineering Journal, 2024)

Root-associated bacterial communities of vegetable Brassica parachinensis enrich pollutant-degrading taxa and functions for enhancing phthalate dissipation - Zhen Wang; Yu-Hong Huang; Minying He; Yan Hu; Xiaohan Xu; Quan-Ying Cai; Ce-Hui Mo; Huixiong Lü (Applied Soil Ecology, 2024)

Retraction Note: Evaluating the trilemma nexus of digital finance, renewable energy consumption, and CO2 emission: evidence from nonlinear ARDL model - Tianyu Mo; Hong Ke (Environmental Science and Pollution Research, 2024)

Simultaneous biodegradation of polycyclic aromatic hydrocarbons and phthalates by bacterial consortium and its bioremediation for complex polluted soil and sewage sludge - Yao-Si Chen; Yu-Hong Huang; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai (Bioresource Technology, 2024)

Enhanced photothermal catalysis for CO2 reduction with H2O by amphoteric metal oxides modified TiO2 - Wenhui Huang; Li Zhang; Jianan Hong; Hongfen Mo; Chenyu Xu; Yanwei Zhang (Waste Disposal & Sustainable Energy, 2024)

Two pairs of new isobenzofuranone enantiomers from a soil-derived fungus Penicillium canescens DWS225 - Jing Wang; Xiao-Qian Wu; Ji-Song Mo; Yu-Fen Tan; Hong-Ping Long; Si-Qian Zhou; Shao Liu; Jing Li; Wen-Xuan Wang (Natural Product Research, 2024)

Occurrence, removal, and prioritization of organic micropollutants in four full-scale wastewater treatment plants in Korea - Sangki Choi; Woorim Lee; Heejong Son; Woongbae Lee; Yegyun Choi; Hoonsik Yeom; Changdong Seo; Hyejin Lee; Yujin Lee; Seung Ji Lim; Sung Ho Chae; Hong Ki Park; et al. (Chemosphere, 2024)

Teleost-specific TLR23 in Takifugu rubripes recruits MyD88 to trigger ERK pathway and promotes antibacterial defense - Yu-ting Du; Hong-qiang Zhang; Yan Li; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Fish & Shellfish Immunology, 2024)

Singapore grouper iridovirus VP146 modulates the cGAS-STING signaling pathway to escape the interferon immune response - Linting Xu; Qiongyue Xu; Weifu Mo; Hong Chen; Siting Wu; Qiwei Qin; Jingguang Wei (Fish & Shellfish Immunology, 2024)

Antioxidant peptide ETT from Isochrysis zhanjiangensis attenuate skin aging by maintaining homeostasis and promoting collagen generation - Yuan-Lin He; Yi Liu; Liyuan Lin; Yinhuan Mo; Huijuan Li; Chunxia Zhou; Pengzhi Hong; Zhong-Ji Qian (Algal Research, 2024)

ML-Net: A Multi-Local Perception Network for Healthy and Bleached Coral Image Classification - Sai Wang; Nan-Lin Chen; Yong-Duo Song; Tuan-Tuan Wang; Jing Wen; Tuan-Qi Guo; Hong-Jin Zhang; Ling Mo; Hao-Ran Ma; Lei Xiang (Journal of Marine Science and Engineering, 2024)
Healthy coral reefs provide diverse habitats for marine life, playing a crucial role in marine ecosystems. Coral health is under threat due to global climate change, ocean pollution, and other environmental stressors, leading to coral bleaching. Coral bleaching disrupts the symbiotic relationship between corals and algae, ultimately impacting the entire marine ecosystem. Processing complex underwater images manually is time-consuming and burdensome for marine experts. To rapidly locate and monitor coral health, deep neural networks are employed for identifying coral categories, which can facilitate the automated processing of extensive underwater imaging data. However, these classification networks may overlook critical classification criteria like color and texture. This paper proposes a multi-local perception network (ML-Net) for image classification of healthy and bleached corals. ML-Net focuses on local features of coral targets, leveraging valuable information for image classification. Specifically, the proposed multi-branch local adaptive block extracts image details through parallel convolution kernels. Then, the proposed multi-scale local fusion block integrates features of different scales vertically, enhancing the detailed information within the deep network. Residual structures in the shallow network transmit local information with more texture and color to the deep network. Both horizontal and vertical multi-scale fusion blocks in deep networks are used to capture and retain local details. We evaluated ML-Net using six evaluation metrics on the Bleached and Unbleached Corals Classification dataset. In particular, ML-Net achieves an ACC result of 86.35, which is 4.36 higher than ResNet and 8.5 higher than ConvNext. Experimental results demonstrate the effectiveness of the proposed modules for coral classification in underwater environments.

Effects of seasonal harvest of kimchi cabbage on microbial and metabolic profiles of kimchi - Soobin Bae; Yun-Jeong Choi; Seong-Eun Park; Eun-Ju Kim; Min Jung Lee; Young Bae Chung; Sung Hee Park; Sung Gi Min; Kang-Mo Ku; Hye-Young Seo; Hong-Seok Son (Food Research International, 2024)

Physiological and genetic responses of the benthic dinoflagellate Prorocentrum lima to polystyrene microplastics - Si-Yuan Xu; Yan-Hang Mo; Yu-Jie Liu; Xiang Wang; Hong-Ye Li; Wei-Dong Yang (Harmful Algae, 2024)

Fishing gear with enhanced drapability and biodegradability: Artificial, eco-friendly fibers inspired by the mussel byssus - Yuri Hong; Ho-Sung Yang; Min Hee Lee; Sinyang Kim; Sung Bae Park; Sung Yeon Hwang; Jeyoung Park; Jun Mo Koo; Dongyeop Oh; Dong Soo Hwang (Chemical Engineering Journal, 2024)

Exposure to microplastics renders immunity of the thick-shell mussel more vulnerable to diarrhetic shellfish toxin-producing harmful algae - Kuan-Kuan Yuan; Ying-Ying Yu; Yan-Hang Mo; Yu-Jie Liu; Wei-Xia Zhang; Jin-Jin Lv; Wei Shi; Guang-Xu Liu; Hong-Ye Li; Wei-Dong Yang (Science of The Total Environment, 2024)

Toxic interactions at the physiological and biochemical levels of green algae under stress of mixtures of three azole fungicides - Li-Tang Qin; Yu-Xue Lei; Min Liu; Hong-Hu Zeng; Yan-Peng Liang; Ling-Yun Mo (Science of The Total Environment, 2024)

Universal occurrence of organophosphate tri-esters and di-esters in marine sediments: Evidence from the Okinawa Trough in the East China Sea - Chan Liang; Yong He; Xiao-Jing Mo; Hong-Xiang Guan; Liang-Ying Liu (Environmental Research, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Variability of marine epifauna assemblages in response to the microhabitat type and thermal stress - Daniela Macias; Seokwoo Hong; Kwon Mo Yang; Junsu Kim; Jeong Ha Kim (Regional Studies in Marine Science, 2024)

Microbial consortium degrading of organic pollutants: Source, degradation efficiency, pathway, mechanism and application - Huixiong Lü; Jia-Lu Wei; Guang-Xuan Tang; Yao-Si Chen; Yu-Hong Huang; Ruiwen Hu; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Qing X. Li (Journal of Cleaner Production, 2024)

Membrane–protected magnetic covalent organic framework for efficient extraction of estrogens in dairy products - Cheng Yang; Zheng–Lian Mo; Qiu–Fang Zhang; Jin–Jie Xu; Xiao–Fang Shen; Yue–Hong Pang (Food Chemistry, 2024)

Population genetic diversity and connectivity of the kelp species Ecklonia cava from the Korean coast - Dong Mun Choi; Seokwoo Hong; Kwon Mo Yang; Young Wook Ko; Jeong Ha Kim (Journal of Applied Phycology, 2024)
Genetic connectivity of kelp populations can provide essential information for estimating their dispersal capability and related perspectives on persistence. We examined population genetic variability to identify connectivity and potential drivers shaping population genetic clusters of Ecklonia cava , a foundation kelp species in the northwest Pacific region. Using microsatellite markers, we analyzed 11 local populations along the Korean coastline from Jeju Island to Ulleungdo. We found that entire study populations were segregated into two genetic groups, inner (south coast populations) and outer (Jeju Island and Ulleungdo) coastal regions, in accordance with current patterns around South Korea and geographical topography. Genetic similarity between the furthest populations (Jeju Island and Ulleungdo) suggest that the dispersal range of E. cava could be largely expanded by the prevalent current. Inter-population genetic structure in the perspectives of isolation-by-distance (IBD) and isolation-by-environment (IBE) revealed that distance and turbidity gradient were both contributors to the gene flow of E. cava . However, different results appeared for a few populations, suggesting that effects of these factors could vary depending on geographic range of populations and surrounding oceanographic conditions. This study suggests that gene flow of E. cava could be driven by multiple seascape factors (ocean currents, coastal topography, distance and sediments) and the interplay among them at a regional scale, which is applicable to other kelp species with diverse scales.

Root-associated bacteria strengthen their community stability against disturbance of antibiotics on structure and functions - Yu-Hong Huang; Yu-Jie Yang; Jie-Yu Li; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Qing X. Li (Journal of Hazardous Materials, 2024)

Wind-induced responses for cable net structures considering punching rate of reflecting panels - De-Xiu Mo; Hong-Nan Li; Qing-Wei Li; Hong-Zhi Zhang (Engineering Structures, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Response and adaptation of rhizosphere microbiome to organic pollutants with enriching pollutant-degraders and genes for bioremediation: A critical review - Huixiong Lü; Guang-Xuan Tang; Yu-Hong Huang; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Yan-Wen Li; Hui Li; Quan-Ying Cai; Qing X. Li (Science of The Total Environment, 2024)

Size and concentration effects of polythene plastic residues on soil physiochemical traits and maize productivity: A three-year appraisal - Ze-Ying Zhao; Peng-Yang Wang; Xiao-Bin Xiong; Momena Irum; Fei Mo; Jing Cao; Ning Wang; Hong-Yan Tao; Meng Hao; Song Wang; Kai-Wen Xiao; Fang-Kun Yang; et al. (Journal of Cleaner Production, 2024)

Conformational isomerization imparts low concentration dependence to multiple resonance thermally activated delayed fluorescence (MR-TADF) emitters - Hao Wu; Yi-Zhong Shi; Mo-Yuan Li; Xiao-Chun Fan; Feng Huang; Kai Wang; Jia Yu; Xiao-Hong Zhang (Chemical Engineering Journal, 2024)

Np-Fe0 addition affects the microstructure and composition of the microwave-sintered lunar soil simulant CLRS-2 - Tian Zhang; Hong Tang; Xiongyao Li; Chuanjiao Zhou; Wen Yu; Bing Mo; Jianzhong Liu; Xiaojia Zeng (Advances in Space Research, 2024)

Crop NDVI time series construction by fusing Sentinel-1, Sentinel-2, and environmental data with an ensemble-based framework - Dairong Chen; Haoxuan Hu; Chunhua Liao; Junyan Ye; Wenhao Bao; Jinglin Mo; Yue Wu; Taifeng Dong; Hong Fan; Jie Pei (Computers and Electronics in Agriculture, 2023)

Developing positively surface-charged carbon dots as “semiconductor electrolyte” for photo-electrochemical H2O2 production based on oxygen reduction - Yong-Shuai Zhang; Hui-Min Duan; Na Wang; Dong-Dong Wei; Liu-Meng Mo; Ning Wang; Xin-Pei Wang; Shuang-Lei Lei; Yuan Zhang; Hong-Yan Wang (Chemical Engineering Journal, 2023)

Deep learning with data preprocessing methods for water quality prediction in ultrafiltration - Jaegyu Shim; Seokmin Hong; Jiye Lee; Seungyong Lee; Young Mo Kim; Kangmin Chon; Sanghun Park; Kyung Hwa Cho (Journal of Cleaner Production, 2023)

Fundicoccus culcitae sp. nov., a novel potential bacteriocin producing bacterium isolated from a spoiled eye mask - Gang Zhou; Lei Gao; Bao-Zhu Fang; Ying-Si Wang; Hong-Bing Tao; Xia Wen; Qian Wang; Xiao-Mo Huang; Qing-Shan Shi; Wen-Jun Li; Xiao-Bao Xie (Antonie van Leeuwenhoek, 2023)

Predicting the shear behavior of reinforced concrete beams with Fe-Based shape memory alloy stirrups - Ki-Nam Hong; Sang-Won Ji; Yeong-Mo Yeon (Engineering Structures, 2023)

Engineering chitin deacetylase AsCDA for improving the catalytic efficiency towards crystalline chitin - Guang Yang; Zhihong Hu; Yuhan Wang; Hongjuan Mo; Shu Liu; Xiaoyue Hou; Xudong Wu; Hong Jiang; Yaowei Fang (Carbohydrate Polymers, 2023)

Forest degradation caused by dwarf bamboo overabundance reduces soil C, N and P stocks in giant panda habitat - Li Mo; Hao Yang; Rong Hou; Wei Wu; Xinqiang Song; Hong Yang; Zhisong Yang; Weichao Zheng; Dunwu Qi (CATENA, 2023)

A pilot study on glutamate receptor and carrier gene variants and risk of childhood autism spectrum - Jun Liu; Jing Yan; Fei Qu; Weiming Mo; Hong Yu; Pingfang Hu; Zengyu Zhang (Metabolic Brain Disease, 2023)

Identification of Diagnostic Markers in Synovial Tissue of Osteoarthritis by Weighted Gene Coexpression Network - Yun-Sen Zhu; Hong Yan; Ting-Ting Mo; Jiang-Nan Zhang; Chang Jiang (Biochemical Genetics, 2023)

Marine debris ingestion by adults and fledglings of Swinhoe's storm petrels in the Republic of Korea - Miran Kim; Mi-jin Hong; Ki-baek Nam; Yang-mo Kim; Chang-uk Park; Youngsoo Kwon (Marine Pollution Bulletin, 2023)

Complexity of SMAX1 signaling during seedling establishment - Pil Joon Seo; Hong Gil Lee; Hye-Young Choi; Sangmin Lee; Chung-Mo Park (Trends in Plant Science, 2023)

IL8 of Takifugu rubripes is a chemokine that interacts with peripheral blood leukocytes and promotes antibacterial defense - Hong-qiang Zhang; Xiao-yan Jin; Xue-peng Li; Mo-fei Li (Fish & Shellfish Immunology, 2023)

Phaeohyphomycosis Caused by Pleurostomophora richardsiae: A Case Report - Yijun Mo; Yao Lu; Bei Wang; Jingjing Wang; Yueru Tian; Hong Liu (Mycopathologia, 2023)

Indoor air quality and its health effects in offices and school buildings in the Yangtze River Delta - Chanjuan Sun; Jingyu Chen; Shijie Hong; Yinping Zhang; Haidong Kan; Zhuohui Zhao; Furong Deng; Xiangang Zeng; Yuexia Sun; Hua Qian; Wei Liu; Jinhan Mo; et al. (Air Quality, Atmosphere & Health, 2023)

Thickness effects of polyethylene and biodegradable film residuals on soil properties and dryland maize productivity - Aimee Grace Uzamurera; Ze-Ying Zhao; Peng-Yang Wang; Yong-Xian Wei; Fei Mo; Rui Zhou; Wen-Li Wang; Fazal Ullah; Aziz Khan; Xiao-Bin Xiong; Meng-Ying Li; Kiprotich Wesly; et al. (Chemosphere, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Rice genotypes and root-associated niches shifted bacterial community in response to pollution of di-(2-ethylhexyl) phthalate (DEHP) for promoting DEHP removal - Cui-Lan Zhu; Hui-Xiong Lü; Yu-Hong Huang; Ji-liang Cheng; Hui Li; Yan-Wen Li; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Quan-Ying Cai (Journal of Hazardous Materials, 2023)

RETRACTED ARTICLE: Evaluating the trilemma nexus of digital finance, renewable energy consumption, and CO2 emission: evidence from nonlinear ARDL model - Tianyu Mo; Hong Ke (Environmental Science and Pollution Research, 2023)

Endophytic Phthalate-degrading Bacillus subtilis N-1-gfp colonizing in soil-crop system shifted indigenous bacterial community to remove di-n-butyl phthalate - Li-Hui Liu; Jia-Yan Zhang; Guang-Xuan Tang; Yu-Hong Huang; Xiang-Qing Xie; Jun Geng; Hui-Xiong Lü; Hui Li; Yan-Wen Li; Ce-Hui Mo; Hai-Ming Zhao; Quan-Ying Cai (Journal of Hazardous Materials, 2023)

Quantifying the effects of submicroscopic metallic iron on VIS–NIR spectra of lunar soils - Yanhua Peng; Siting Zhang; Hong Tang; Zhuang Guo; Wen Yu; Guozhu Chen; Chen Li; Bingkui Miao; Bing Mo; Encheng He; Ting Zhou; Zhipeng Xia; et al. (Icarus, 2023)

How the Wild Sugarcane Resource Miscanthus floridulus Responds to Low-Temperature Stress: A Physiological and Transcriptomic Analysis - Hong-Li Yang; Zhi-Jun Guo; Lu Jiang; Jun-Jun He; Qing Liu; Mo Chen; Xing-Hua Yu; Xian-Hong Wang; Qing-Hui Yang (Sugar Tech, 2023)

Oleuropein induces apoptosis in colorectal tumor spheres via mitochondrial fission - Da Yeon Kim; Sangmi Park; Jisoo Yun; Woongbi Jang; Vinoth Kumar Rethineswaran; Le Thi Hong Van; Ly Thanh Truong Giang; Jaewoo Choi; Hye ji Lim; Sang-Mo Kwon (Molecular & Cellular Toxicology, 2023)

Divergent responses in the gut microbiome and liver metabolome to ammonia stress in three freshwater turtles - Qin-Yuan Meng; Dong-Mei Mo; Han Li; Wan-Ling Wang; Hong-Liang Lu (Science of The Total Environment, 2023)

Adaptation of bacterial community in maize rhizosphere for enhancing dissipation of phthalic acid esters in agricultural soil - Yu-Hong Huang; Yu-Jie Yang; Xiaolian Wu; Cui-Lan Zhu; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Qing X. Li (Journal of Hazardous Materials, 2023)

Co-exposure to phenols and phthalates during pregnancy with the difference of body size in twins at one month old - Hong Mei; Langjing Deng; Jinying Xie; Xiaojie Li; Nanxin Wu; Liqin Hu; Guangtong Huang; Fanyu Mo; Da Chen; Han Xiao; Pan Yang (Chemosphere, 2023)

Modeling study on the roles of the deposition and transport of PM2.5 in air quality changes over central-eastern China - Lei Zhang; Jianjun He; Sunling Gong; Xiaomei Guo; Tianliang Zhao; Huizheng Che; Hong Wang; Chunhong Zhou; Jingyue Mo; Ke Gui; Yu Zheng; Lei Li; et al. (Journal of Environmental Sciences, 2023)

Effect of solvent swelling with different enhancement methods on the microstructure and pyrolysis performance of Hefeng subbituminous coal - Hui Kan; Yue Wang; Wen-Long Mo; Xian-Yong Wei; Hong-Yu Mi; Kong-Jun Ma; Mei-Xia Zhu; Wen-Cang Guo; Jia Guo; Jun-Min Niu; Xing Fan (Fuel, 2023)

Effect of sequential thermal dissolution on the structure and pyrolysis characteristics of Naomaohu lignite - Xiao-Bo Hu; Hao Xu; Wen-Long Mo; Xing Fan; Wen-Cang Guo; Jia Guo; Jun-Min Niu; Hong-Yu Mi; Ya-Ya Ma; Xian-Yong Wei (Fuel, 2023)

A novel C1qDC (PoC1qDC) with a collagen domain in Paralichthys olivaceus mediates complement activation and against bacterial infection - Mo-fei Li; Hong-qiang Zhang; Jin-sheng Sun (Fish & Shellfish Immunology, 2023)

Gender-specific effects of prenatal mixed exposure to serum phthalates on neurodevelopment of children aged 2–3 years:the Guangxi Birth Cohort Study - Yuan Zheng; Longman Li; Hong Cheng; Shengzhu Huang; Xiuming Feng; Lulu Huang; Luyun Wei; Dehao Cao; Sida Wang; Long Tian; Weijun Tang; Caitong He; et al. (Environmental Science and Pollution Research, 2022)

Overexpression of the Polygonum cuspidatum PcDREB2A Gene Encoding a DRE-Binding Transcription Factor Enhances the Drought Tolerance of Transgenic Arabidopsis thaliana - Hongyan Hu; Xiaowei Wang; Zhijun Wu; Mo Chen; Tuanyao Chai; Hong Wang (Journal of Plant Biology, 2022)

Sargassum horneri Extract Alleviates Testosterone-Induced Benign Prostatic Hyperplasia In vitro and In vivo - Yae-Ji Kim; Kyung-Hyun Kim; Hyun-Yong Kim; Sung-Mo Kang; Geum-Lan Hong; Hui-Ju Lee; Soon-Sung Lim; Ju-Young Jung (Journal of Aquatic Food Product Technology, 2022)

The Critically Endangered Hainan Gibbon (Nomascus hainanus) Population Increases but not at the Maximum Possible Rate - Guioqi Liu; Xueli Lu; Zhao Liu; Zhi Xie; Xuming Qi; Jiang Zhou; Xiaojiang Hong; Yanni Mo; Bosco P. L. Chan; Colin A. Chapman; Zhigang Jiang (International Journal of Primatology, 2022)
With the ongoing global biodiversity crisis in the Anthropocene, it is critical to understand how to save endangered species to “bend the curve” of biodiversity decline. The Hainan gibbon ( Nomascus hainanus ) is a Critically Endangered species that is endemic to Hainan Island. We performed two synchronized total count surveys in Hainan Tropic Rain Forest National Park in November and December of 2020 and 2021 by locating gibbon groups from their morning calls and conducting detailed counts in all potential habitat fragments. We compared our findings with existing data to model the population trend, and analyzed the potential and realized reproductive potentials. We found 5 groups with a total of 33 gibbons in 2020 and 35 in 2021, including 4 and 6 solitary individuals respectively. This is an increase of 169% since 2003, when there were 13 individuals with 2 groups and 2 solitary individuals. Logistic and linear curves fitted the 2003-2021 population census data equally well. Although the population is growing, it has not realized its full reproductive potential (when all adult females give births at 24-month intervals), suggesting that external factors like available habitat, as well as nutritional, physiological, and behavioral factors may be limiting the population. The gibbon’s recovery demonstrates that establishing a nature reserve with regular patrols, banning logging, curbing poaching, and environmental education have been effective. Because the Hainan gibbon population is still extremely small, carefully planned conservation actions, including an ambitious forest restoration program, will be needed to ensure the species’ continued survival.

Causal Effect of Genetically Determined Blood Copper Concentrations on Multiple Diseases: A Mendelian Randomization and Phenome-Wide Association Study - Xiuming Feng; Wenjun Yang; Lulu Huang; Hong Cheng; Xiaoting Ge; Gaohui Zan; Yanli Tan; Lili Xiao; Chaoqun Liu; Xing Chen; Zengnan Mo; Longman Li; et al. (Phenomics, 2022)

Estimating and mapping snow hazard based on at-site analysis and regional approaches - H. M. Mo; W. Ye; H. P. Hong (Natural Hazards, 2022)

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

The combined toxicity and mechanism of multi-walled carbon nanotubes and nano zinc oxide toward the cabbage - Mo Hong; Ji-Lai Gong; Wei-Cheng Cao; Rong Fang; Zhe Cai; Jun Ye; Zeng-Ping Chen; Wang-Wang Tang (Environmental Science and Pollution Research, 2022)

Correction to: Variations in methyl bromide concentration with distance and time during quarantine fumigation - Min-Goo Park; Hyoung-ho Mo; Young-Seoub Hong; Chung Gyoo Park; Dong-Chul Gu (Environmental Monitoring and Assessment, 2021)

Pancreatic cancer pathology viewed in the light of evolution - Michaël Noë; Seung-Mo Hong; Laura D. Wood; Elizabeth D. Thompson; Nicholas J. Roberts; Michael G. Goggins; Alison P. Klein; James R. Eshleman; Scott E. Kern; Ralph H. Hruban (Cancer and Metastasis Reviews, 2021)
One way to understand ductal adenocarcinoma of the pancreas (pancreatic cancer) is to view it as unimaginably large numbers of evolving living organisms interacting with their environment. This “evolutionary view” creates both expected and surprising perspectives in all stages of neoplastic progression. Advances in the field will require greater attention to this critical evolutionary prospective.

Variations in methyl bromide concentration with distance and time during quarantine fumigation - Min-Goo Park; Young-Seoub Hong; Chung Gyoo Park; Dong-Chul Gu; Hyoung-ho Mo (Environmental Monitoring and Assessment, 2021)
Methyl bromide (MB) is a highly toxic and ozone-depleting substance and should be replaced. Worker exposure to high MB concentrations during fumigation has been previously reported. However, variations in MB concentration as a function of distance from fumigated objects or of time after degassing have not been reported so far. In this study, air samples were collected at various distances from fumigated objects (oranges, wood in containers, and wood in tarpaulin) during injection and degassing and analyzed via gas chromatography according to the Occupational Safety and Health Agency method. In addition, MB concentrations were directly measured over time using a gas detector during degassing. Non-linear regression analysis of the logarithmically transformed data indicated a clear decrease in MB concentration with distance as well as time. Non-linear regression models were constructed to describe the decrease in MB concentration with distance from the objects and with time during degassing ( P < 0.05 for all models). The results of this study could aid in establishing appropriate safety guidelines, and hence, in preventing risks related to MB exposure.

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Generation of Hepatic Progenitor Cells from the Primary Hepatocytes of Nonhuman Primates Using Small Molecules - Da Hee Hong; Changhee Lee; Yohan Kim; Seung Bum Lee; Su-Cheol Han; Sung Joo Kim; Heung-Mo Yang; Dongho Choi; Jaemin Jeong; Kiyoung Ryu (Tissue Engineering and Regenerative Medicine, 2021)

A novel apoptosis probe, cyclic ApoPep-1, for in vivo imaging with multimodal applications in chronic inflammatory arthritis - In-Seop So; Jin Hee Kang; Jung Wan Hong; Shijin Sung; Al Faruque Hasan; Keum Hee Sa; Seung Woo Han; In San Kim; Young Mo Kang (Apoptosis, 2021)

Preliminary report on the improved resistance towards Pseudomonas syringae pv. actinidiae of cultivated kiwifruit (Actinidia chinensis) when grafted onto wild Actinidia guilinensis rootstock in vitro - Fa-ming Wang; Jie-wei Li; Kai-yu Ye; Hong-juan Gong; Ping-ping Liu; Qiao-sheng Jiang; Bei-bei Qi; Quan-hui Mo (Journal of Plant Pathology, 2021)

Silencing of Long Non-coding RNA GAS5 Suppresses Neuron Cell Apoptosis and Nerve Injury in Ischemic Stroke Through Inhibiting DNMT3B-Dependent MAP4K4 Methylation - Yiming Deng; Duanduan Chen; Feng Gao; Hong Lv; Guojun Zhang; Xuan Sun; Lian Liu; Dapeng Mo; Ning Ma; Ligang Song; Xiaochuan Huo; Tianyi Yan; et al. (Translational Stroke Research, 2020)

Auramine O in foods and spices determined by an UPLC-MS/MS method - Thanh-Thien Tran-Lam; Mo Bui Thi Hong; Giang Truong Le; Phuong Duc Luu (Food Additives & Contaminants Part B-Surveillance, 2020)

Engineered M13 Peptide Carrier Promotes Angiogenic Potential of Patient-Derived Human Cardiac Progenitor Cells and In Vivo Engraftment - Woong Bi Jang; Seung Taek Ji; Ji Hye Park; Yeon-Ju Kim; Songhwa Kang; Da Yeon Kim; Na-Kyung Lee; Jin Su Kim; Hye Ji Lim; Jaewoo Choi; Thi Hong Van Le; Thanh Truong Giang Ly; et al. (Tissue Engineering and Regenerative Medicine, 2020)

Formation of $${\text {CaCO}}_3$$ varieties from a carbonated aqueous solution - Hong-Mo Ryang; Hak-Chol Sim (Carbonates and Evaporites, 2019)

Temporal and spatial dynamics of phenology along the North–South Transect of Northeast Asia - Yunhua Mo; Shulin Chen; Jiaxin Jin; Xuehe Lu; Hong Jiang (International Journal of Remote Sensing, 2019)

Joint toxicity of six common heavy metals to Chlorella pyrenoidosa - Ling-Yun Mo; Dan-Na Zhao; Meng Qin; Li-Tang Qin; Hong-Hu Zeng; Yan-Peng Liang (Environmental Science and Pollution Research, 2019)

Involvement of glutamate receptors in regulating calcium influx in rice seedlings under Cr exposure - Yan-Hong Li; Xiao-Zhang Yu; Ling-Yun Mo; Yu-Juan Lin; Qing Zhang (Ecotoxicology, 2019)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

Detection of lncRNA-mRNA interaction modules by integrating eQTL with weighted gene co-expression network analysis - Xing-Bo Mo; Long-Fei Wu; Xin Lu; Xiao-Wei Zhu; Wei Xia; Lan Wang; Pei He; Peng-Fei Bing; Yong-Hong Zhang; Fei-Yan Deng; Shu-Feng Lei (Functional & Integrative Genomics, 2019)

Contribution of Cathepsin L to Autolysis of Sea Cucumber Stichopus japonicus Intestines - Jia-Nan Yan; Xiao-Kun Guo; Yue Tang; Ao-Ting Li; Zhi-Mo Zhu; Xiao-Qian Chai; Xiu-Hong Duan; Hai-Tao Wu (Journal of Aquatic Food Product Technology, 2019)

Induction and identification of tetraploid Hedychium coronarium through thin cell layer culture - Hong-Yan Tu; Ai-Ling Zhang; Wang Xiao; Ya-Rou Lin; Jun-Hui Shi; Yong-Wei Wu; Si-Tong Wu; Chun-Hui Zhong; Shui-Xiu Mo (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Direct and legacy effects of herbivory on growth and physiology of a clonal plant - Bi-Cheng Dong; Mo-Zhu Wang; Rui-Hua Liu; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Biological Invasions, 2018)

Efficient generation of functional cardiomyocytes from human umbilical cord-derived virus-free induced pluripotent stem cells - Kai Hong Wu; Su Yun Wang; Qian Ru Xiao; Yu Yang; Ning Ping Huang; Xu Ming Mo; Jian Sun (Cell and Tissue Research, 2018)

A WRKY transcription factor, PcWRKY33, from Polygonum cuspidatum reduces salt tolerance in transgenic Arabidopsis thaliana - Wenqi Bao; Xiaowei Wang; Mo Chen; Tuanyao Chai; Hong Wang (Plant Cell Reports, 2018)

Variation in accumulation, transport, and distribution of phthalic acid esters (PAEs) in soil columns grown with low- and high-PAE accumulating rice cultivars - Yang Wu; Xue-Xue Chen; Ting-Kai Zhu; Xing Li; Xiao-Hong Chen; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Ming-Hung Wong (Environmental Science and Pollution Research, 2018)

Effects of Oxalic Acid on Arsenic Uptake and the Physiological Responses of Hydrilla verticillata Exposed to Different Forms of Arsenic - Wen Zheng; Zheng-yan Zhong; Hong-bin Wang; Hai-juan Wang; Dong-mo Wu (Bulletin of Environmental Contamination and Toxicology, 2018)

Correction to: Engineered M13 Nanofiber Accelerates Ischemic Neovascularization by Enhancing Endothelial Progenitor Cells - Jun Hee Lee; Sung Wook Kim; Seung Taek Ji; Yeon Ju Kim; Woong Bi Jang; Jin-Woo Oh; Jaeho Kim; So Young Yoo; Sang Hong Baek; Sang-Mo Kwon (Tissue Engineering and Regenerative Medicine, 2018)

Correlation analyses revealed global microRNA–mRNA expression associations in human peripheral blood mononuclear cells - Lan Wang; Jiang Zhu; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Xiao-Wei Zhu; Wei Xia; Fang-Fei Xie; Pei He; Peng-Fei Bing; Ying-Hua Qiu; Xiang Lin; et al. (Molecular Genetics and Genomics, 2018)

Multiple correlation analyses revealed complex relationship between DNA methylation and mRNA expression in human peripheral blood mononuclear cells - Fang-Fei Xie; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Hong Zhu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiao-Wei Zhu; Wei Xia; Lan Wang; et al. (Functional & Integrative Genomics, 2018)

Engineered M13 Nanofiber Accelerates Ischemic Neovascularization by Enhancing Endothelial Progenitor Cells - Jun Hee Lee; Sung Wook Kim; Seung Taek Ji; Yeon Ju Kim; Woong Bi Jang; Jin-Woo Oh; Jaeho Kim; So Young Yoo; Sang Hong Beak; Sang-Mo Kwon (Tissue Engineering and Regenerative Medicine, 2017)

A nationwide study of the incidence rate of herb-induced liver injury in Korea - Jung-Hyo Cho; Dal-Seok Oh; Sang-Hoon Hong; Heung Ko; Nam-Hun Lee; Sang-Eun Park; Chang-Woo Han; Seung-Mo Kim; Young-Chul Kim; Kang-San Kim; Chang-Won Choi; Seon-My Shin; et al. (Archives of Toxicology, 2017)

Toxicological effects of microcystin-LR on earthworm (Eisenia fetida) in soil - Hong-Fei Wen; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Lei Chen; Quan-Ying Cai; Hui Li; Ce-Hui Mo; Dong-Mei Zhou; Ming-Hung Wong (Biology and Fertility of Soils, 2017)

Using remote sensing information to estimate snow hazard and extreme snow load in China - H. M. Mo; H. P. Hong; F. Fan (Natural Hazards, 2017)

Effects of perceived job insecurity on depression, suicide ideation, and decline in self-rated health in Korea: a population-based panel study - Min-Seok Kim; Yun-Chul Hong; Ji-Hoo Yook; Mo-Yeol Kang (International Archives of Occupational and Environmental Health, 2017)

Comparative transcriptomes and reciprocal best hit analysis revealed potential pigment genes in two color forms of Tetranychus urticae - Yi-Dan Mo; Si-Xia Yang; Jing-Yu Zhao; Peng-Yu Jin; Xiao-Yue Hong (Experimental and Applied Acarology, 2017)

Bacillus zanthoxyli sp. nov., a novel nematicidal bacterium isolated from Chinese red pepper (Zanthoxylum bungeanum Maxim) leaves in China - Ma Li; Cao Yong Hong; Wang Xiao Yan; Zheng Shuai Chao; Yang Cheng Gang; Duo Jin Ling; Zhou Xing Kui; Xi Jia Qin; Zhu Ming Liang; Mo Ming He (Antonie van Leeuwenhoek, 2017)

Enhanced dissipation of DEHP in soil and simultaneously reduced bioaccumulation of DEHP in vegetable using bioaugmentation with exogenous bacteria - Hai-Ming Zhao; Rui-Wen Hu; He-Biao Huang; Hong-Fei Wen; Huan Du; Yan-Wen Li; Hui Li; Quan-Ying Cai; Ce-Hui Mo; Jie-Sheng Liu; Ming-Hung Wong (Biology and Fertility of Soils, 2017)

Analysis of diagnosis and treatment of lipoblastomatosis - Zhiqiang Mo; Xianghui Xie; Huanmin Wang; Hong Qin; Wei Han; Xiaosong Li (Science China Life Sciences, 2017)

Two-Stage Prediction on Effects of Mixtures Containing Phenolic Compounds and Heavy Metals on Vibrio qinghaiensis sp. Q67 - Ling-Yun Mo; Jie Liu; Li-Tang Qin; Hong-Hu Zeng; Yan-Peng Liang (Bulletin of Environmental Contamination and Toxicology, 2017)

Single Nucleotide Polymorphisms in SLC19A1 and SLC25A9 Are Associated with Childhood Autism Spectrum Disorder in the Chinese Han Population - Jun Liu; Weiming Mo; Zengyu Zhang; Hong Yu; Aiping Yang; Fei Qu; Pingfang Hu; Zhuo Liu; Shihu Wang (Journal of Molecular Neuroscience, 2017)

Molecular and cellular insights into Zika virus-related neuropathies - Kai Zhou; Long Wang; Di Yu; Hesuyuan Huang; Hong Ji; Xuming Mo (Journal of NeuroVirology, 2017)

Effects of Glycyrrhetinic Acid on GSH Synthesis Induced by Realgar in the Mouse Hippocampus: Involvement of System X AG - $$ X_{AG^{-}} $$ , System X C - $$ X_{C^{-}} $$ , MRP-1, and Nrf2 - Yan-lei Wang; Mo Chen; Tao-guang Huo; Ying-hua Zhang; Ying Fang; Cong Feng; Shou-yun Wang; Hong Jiang (Molecular Neurobiology, 2017)

Purification and sequence characterization of chondroitin sulfate and dermatan sulfate from fishes - Na Lin; Xiaoli Mo; Yang Yang; Hong Zhang (Glycoconjugate Journal, 2017)

A novel thymidine phosphorylase mutation in a Chinese MNGIE patient - Hui-Fang Wang; Juan Wang; Yan-Ling Wang; Jian-Jian Fan; Gui-Lin Mo; Feng-Yin Gong; Zhi-Ming Chai; Jin Zhang; Hua-Xing Meng; Chang-Xin Li; Jun-Hong Guo; Chuan-Qiang Pu (Acta Neurologica Belgica, 2017)

Patterns of SSR variation in bread wheat (Triticum aestivum L.) seeds under ex situ genebank storage and accelerated ageing - Yong-Bi Fu; Mo-Hua Yang; Carolee Horbach; Dallas Kessler; Axel Diederichsen; Frank M. You; Hong Wang (Genetic Resources and Crop Evolution, 2017)

Design, synthesis, and antimicrobial activities of new tanshinone IIA esters - Lin-Wei Zeng; Chang-Xin Zhou; Jia-Dong Liu; Chang-Hong Liu; Jian-Xia Mo; A-Fang Hou; Wei Yao; Zhen-Zhen Wang; Li-She Gan (Natural Product Research, 2016)

Extreme snow hazard and ground snow load for China - H. M. Mo; L. Y. Dai; F. Fan; T. Che; H. P. Hong (Natural Hazards, 2016)

Predicting the Binding Affinity of ERβ Ligands Based on a Novel Variable Selection Method - Hong-Yan Liu; Fei Zhang; Li-Tang Qin; Zhong-Sheng Yi; Xiu-Li Wang; Ling-Yun Mo (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Polygonatum stenophyllum improves menopausal obesity via regulation of lipolysis-related enzymes - Ji Eun Lee; Eun-Jung Kim; Mi Hye Kim; Jongki Hong; Woong Mo Yang (Journal of Natural Medicines, 2016)

Molecular weight controllable degradation of Laminaria japonica polysaccharides and its antioxidant properties - Shenghua Zha; Qingsheng Zhao; Bing Zhao; Jie Ouyang; Jianling Mo; Jinjin Chen; Lili Cao; Hong Zhang (Journal of Ocean University of China, 2016)

Inhibitory effects of Leonurus sibiricus on weight gain after menopause in ovariectomized and high-fat diet-fed mice - Jangseon Kim; Mi Hye Kim; You Yeon Choi; Jongki Hong; Woong Mo Yang (Journal of Natural Medicines, 2016)

Chloride ion-driven transformation from Ag3PO4 to AgCl on the hydroxyapatite support and its dual antibacterial effect against Escherichia coli under visible light irradiation - Xiaoting Hong; Min Li; Shengdao Shan; K. S. Hui; Mingyue Mo; Xiaoli Yuan (Environmental Science and Pollution Research, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

Autoimmunity and dysmetabolism of human acquired immunodeficiency syndrome - Yan-Mei Huang; Xue-Zhi Hong; Jia-Hua Xu; Jiang-Xi Luo; Han-You Mo; Hai-Lu Zhao (Immunologic Research, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

GOLPH3 Mediated Golgi Stress Response in Modulating N2A Cell Death upon Oxygen-Glucose Deprivation and Reoxygenation Injury - Ting Li; Hong You; Xiaoye Mo; Wenfang He; Xiangqi Tang; Zheng Jiang; Shiyu Chen; Yang Chen; Jie Zhang; Zhiping Hu (Molecular Neurobiology, 2016)

Sulfuretin induces osteoblast differentiation through activation of TGF-β signaling - No-Joon Song; So-Mi Kwon; Suji Kim; Hyang-Jin Yoon; Cho-Rong Seo; Byunghyun Jang; Seo-Hyuk Chang; Jin-Mo Ku; Jeong-Soo Lee; Ki-Moon Park; Joung-Woo Hong; Geun Hyung Kim; et al. (Molecular and Cellular Biochemistry, 2015)

Erratum to: Characterization of Physa acuta expressed sequence tags and transcript mining following cadmium exposure - Ji Eun Jeong; Bharat Bhusan Patnaik; Se Won Kang; Hee-Ju Hwang; So Young Park; Tae Hun Wang; Eun Bi Park; Jae Bong Lee; Myung-Mo Nam; Yong Hun Jo; Yeon Soo Han; Jun-Sang Lee; et al. (Genes & Genomics, 2015)

Expressed sequence tag analysis and annotation of genetic information from the freshwater clam, Pisidium (Neopisidium) coreanum endemic to Korea - Ji Eun Jeong; Se Won Kang; Hee-Ju Hwang; So Young Park; Bharat Bhusan Patnaik; Changmu Kim; Soonok Kim; Myung-Mo Nam; Jae Bong Lee; Tae Hun Wang; Eun Bi Park; Sun Shin Yi; et al. (Genes & Genomics, 2015)

Characterization of Physa acuta expressed sequence tags and transcript mining following cadmium exposure - Ji Eun Jeong; Bharat Bhusan Patnaik; Se Won Kang; Hee-Ju Hwang; So Young Park; Tae Hun Wang; Eun Bi Park; Jae Bong Lee; Myung-Mo Nam; Yong Hun Jo; Yeon Soo Han; Jun-Sang Lee; et al. (Genes & Genomics, 2015)

Cucurbitacin D induces cell cycle arrest and apoptosis by inhibiting STAT3 and NF-κB signaling in doxorubicin-resistant human breast carcinoma (MCF7/ADR) cells - Jin Mo Ku; Soon Re Kim; Se Hyang Hong; Han-Seok Choi; Hye Sook Seo; Yong Cheol Shin; Seong-Gyu Ko (Molecular and Cellular Biochemistry, 2015)

Three-dimensional culture of mesenchymal stem cells - Jong Kyu Hong; Jisoo Yun; Hyunyun Kim; Sang-Mo Kwon (Tissue Engineering and Regenerative Medicine, 2015)

MIR137 Regulates Starvation-Induced Autophagy by Targeting ATG7 - Yuecheng Zeng; Gang Huo; Yongbiao Mo; Wentao Wang; Hong Chen (Journal of Molecular Neuroscience, 2015)

Linear regression model for predicting interactive mixture toxicity of pesticide and ionic liquid - Li-Tang Qin; Jie Wu; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang (Environmental Science and Pollution Research, 2015)

Snow hazard estimation and mapping for a province in northeast China - H. M. Mo; F. Fan; H. P. Hong (Natural Hazards, 2015)

Study of GOLPH3: a Potential Stress-Inducible Protein from Golgi Apparatus - Ting Li; Hong You; Jie Zhang; Xiaoye Mo; Wenfang He; Yang Chen; Xiangqi Tang; Zheng Jiang; Ranran Tu; Liuwang Zeng; Wei Lu; Zhiping Hu (Molecular Neurobiology, 2014)

Biological control of Ralstonia wilt, Phytophthora blight, Meloidogyne root-knot on bell pepper by the combination of Bacillus subtilis AR12, Bacillus subtilis SM21 and Chryseobacterium sp. R89 - Hong-Xia Liu; Shi-Mo Li; Yu-Ming Luo; Lai-Xin Luo; Jian-Qiang Li; Jian-Hua Guo (European Journal of Plant Pathology, 2014)

scFv antibodies against infectious bursal disease virus isolated from a combinatorial antibody library by flow cytometry - Li-Ming Xu; Tian-He Li; Bing Zhou; Mo Guo; Miao Liu; Jing-Zhuang Zhao; Hong-Wei Cao; De-Shan Li (Biotechnology Letters, 2014)

Single primary fetal lung cells generate alveolar structures in vitro - Shengliang Zhang; Xin Zhou; Tie Chen; Yanna Shang; Ran Lu; Dongqin Yin; Jin Liu; Hong Xu; Xianming Mo (In Vitro Cellular & Developmental Biology - Animal, 2014)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Fertilizer N uptake of paddy rice in two soils with different fertility under experimental warming with elevated CO2 - Hong-Shik Nam; Jin-Hyeob Kwak; Sang-Sun Lim; Woo-Jung Choi; Sun-Il Lee; Dong-Suk Lee; Kwang-Seung Lee; Han-Yong Kim; Sang-Mo Lee; Miwa Matsushima (Plant and Soil, 2013)

Bupivacaine-induced cytotoxicity related to endoplasmic reticulum stress pathways in SH-SY5Y cells - Young-Keun Chae; Sung Mo Kang; Yong-Ho Kim; Eun-Hee Jang; Ju-Hee Kang; Hong-Sik Lee (Molecular & Cellular Toxicology, 2013)

Climate warming-induced upward shift of Moso bamboo population on Tianmu Mountain, China - Xin-zhang Song; Chang-hui Peng; Guo-mo Zhou; Hong Jiang; Wei-feng Wang; Wen-hua Xiang (Journal of Mountain Science, 2013)

Phylogenetic diversity of bacterial endophytes of Panax notoginseng with antagonistic characteristics towards pathogens of root-rot disease complex - Li Ma; Yong Hong Cao; Ming Hui Cheng; Ying Huang; Ming He Mo; Yong Wang; Jian Zhong Yang; Fa Xiang Yang (Antonie van Leeuwenhoek, 2013)

Preparation of leaf mesophyll protoplasts for transient gene expression in Brachypodium distachyon - Shin-Young Hong; Pil Joon Seo; Shin-Hae Cho; Chung-Mo Park (Journal of Plant Biology, 2012)

Polycyclic aromatic hydrocarbons in animal-based foods from Shanghai: bioaccessibility and dietary exposure - Ying-Xin Yu; Liang Chen; Dan Yang; Yu-Ping Pang; Shao-Huan Zhang; Xin-Yu Zhang; Zhi-Qiang Yu; Ming-Hong Wu; Jia-Mo Fu (Food Additives & Contaminants: Part A, 2012)

Effects of polymorphisms in the 3′ untranslated region of the porcine PPARGC1A gene on muscle fiber characteristics and meat quality traits - Jun-Seong Lee; Jun-Mo Kim; Jae-Sang Hong; Kyu-Sang Lim; Ki-Chang Hong; Young Sik Lee (Molecular Biology Reports, 2012)

5-Phenylselenyl- and 5-methylselenyl-methyl-2′-deoxyuridine induce oxidative stress, DNA damage, and caspase-2-dependent apoptosis in cancer cells - Byeong Mo Kim; Ambadas B. Rode; Eun Jong Han; In Seok Hong; Sung Hee Hong (Apoptosis, 2012)

Combined Toxicity of the Mixtures of Phenol and Aniline Derivatives to Vibrio qinghaiensis sp.-Q67 - Ling-Yun Mo; Shu-Shen Liu; Yi-Nian Zhu; Hai-Ling Liu; Hong-Yan Liu; Zhong-Sheng Yi (Bulletin of Environmental Contamination and Toxicology, 2011)

The roles of ascorbic acid and glutathione in symptom alleviation to SA-deficient plants infected with RNA viruses - Shao-Dong Wang; Feng Zhu; Shu Yuan; Hui Yang; Fei Xu; Jing Shang; Mo-Yun Xu; Shu-Dan Jia; Zhong-Wei Zhang; Jian-Hui Wang; De-Hui Xi; Hong-Hui Lin (Planta, 2011)

Tracing origins of sewage and organic matter using dissolved sterols in Masan and Haengam Bay, Korea - Hyo Jin Lee; Sang Hee Hong; Moonkoo Kim; Sung Yong Ha; Soon Mo An; Won Joon Shim (Ocean Science Journal, 2011)

A broad-spectrum, efficient and nontransgenic approach to control plant viruses by application of salicylic acid and jasmonic acid - Jing Shang; De-Hui Xi; Fei Xu; Shao-Dong Wang; Sen Cao; Mo-Yun Xu; Ping-Ping Zhao; Jian-Hui Wang; Shu-Dan Jia; Zhong-Wei Zhang; Shu Yuan; Hong-Hui Lin (Planta, 2011)

Sequential caspase-2 and caspase-8 activation is essential for saikosaponin a-induced apoptosis of human colon carcinoma cell lines - Byeong Mo Kim; Sung Hee Hong (Apoptosis, 2011)

Rapid simultaneous screening of seven clinically important enteric pathogens using a magnetic bead based DNA microarray - Hong Sun; Qiu-Hua Mo; Ji-Can Lin; Ze Yang; Cheng-Ning Tu; Da-Yong Gu; Lei Shi; Wei-Ping Lu (World Journal of Microbiology and Biotechnology, 2011)

N,N-Dimethyl phytosphingosine sensitizes HL-60/MX2, a multidrug-resistant variant of HL-60 cells, to doxorubicin-induced cytotoxicity through ROS-mediated release of cytochrome c and AIF - Byeong Mo Kim; Yun Jung Choi; Yong Heon Lee; Young Ae Joe; Sung Hee Hong (Apoptosis, 2010)

Identification and molecular characterization of a Brachypodium distachyon GIGANTEA gene: functional conservation in monocot and dicot plants - Shin-Young Hong; Sangmin Lee; Pil Joon Seo; Moon-Sik Yang; Chung-Mo Park (Plant Molecular Biology, 2010)

Gibberellin production and phosphate solubilization by newly isolated strain of Acinetobacter calcoaceticus and its effect on plant growth - Sang-Mo Kang; Gil-Jae Joo; Muhammad Hamayun; Chae-In Na; Dong-Hyun Shin; Hak Youn Kim; Jin-Kyu Hong; In-Jung Lee (Biotechnology Letters, 2009)

p63 and p73 expression in extrahepatic bile duct carcinoma and their clinical significance - Seung-Mo Hong; HyungJun Cho; Christopher A. Moskaluk; Eunsil Yu; Alexander I. Zaika (Journal of Molecular Histology, 2007)

Compounds inhibitory to nematophagous fungi produced by Bacillus sp. strain H6 isolated from fungistatic soil - Lei Li; Minghe Mo; Qing Qu; Hong Luo; Keqin Zhang (European Journal of Plant Pathology, 2007)

Crustal Structure of the Southern Korean Peninsula from Seismic Waves Generated by Large Explosions in 2002 and 2004 - Ki Young Kim; Jung Mo Lee; Wooil Moon; Chang-Eob Baag; Heeok Jung; Myung Ho Hong (Pure and Applied Geophysics, 2007)

Expressions of polypeptide: N-acetylgalactosaminyltransferase in leukemia cell lines during 1,25-dihydroxyvitamin D3 induced differentiation - Hao Qiu; Xiang-Hong Guo; Jian-Hua Mo; Mei-Fang Jin; Shi-Liang Wu; Hui-Li Chen (Glycoconjugate Journal, 2006)

Molecular analysis of early rice stamen development using organ-specific gene expression profiling - Xiao-Chun Lu; Hua-Qin Gong; Mo-Li Huang; Su-Lan Bai; Yang-Bo He; Xizeng Mao; Zhi Geng; Song-Gang Li; Liping Wei; Jie-Shuai Yuwen; Zhi-Hong Xu; Shu-Nong Bai (Plant Molecular Biology, 2006)

Litterfall Dynamics of an Evergreen Broadleaf Forest and a Pine Forest in the Subtropical Region of China - Zhi An Li; Bi Zou; Han-ping Xia; Hai Ren; Jiang-ming Mo; Hong Weng (Forest Science, 2005)
Monthly litterfall was monitored over a 10-year period from an evergreen broadleaf forest (EBF) and a pine forest (PF) in subtropical South China. During this period, litter was also collected bimonthly from the forest floor for 2 years. Total annual litterfall in EBF fluctuated around 9 Mg ha−1 with leaves, branches, and miscellanea accounting for 52.5%, 22.2%, and 25.3%, respectively. Total annual litterfall alternated between high and low values in consecutive years. Storms and pest outbreaks were responsible for most of the peaks in both monthly and annual litterfall. Litter from each of 43 species was recorded, but 9 species contributed about 85% of total litterfall. Dominant species shed their leaves in a more regular pattern with peaks mainly from Jan. to Mar. Pine forest (Pinus massoniana) produced much less litterfall than EBF, with a mean of 2.7 Mg ha−1. Here, leaves accounted for 73.2% of total litterfall, branches only 11.4%, and miscellanea 15.4%. Litter on the ground amounted to 5.2 Mg ha−1 in EBF and 2.9 Mg ha−1 in PF. The results show that this climax forest has much higher litterfall and forest floor mass than the pine forest, and litterfall is rather stable with regard to annual variation. FOR. SCI. 51(6):608–615.

Heme-copper/dioxygen adduct formation relevant to cytochrome c oxidase: spectroscopic characterization of [(6L)FeIII-(O22?)-CuII]+ - Reza A. Ghiladi; Hong-wei Huang; Pierre Monne-Loccoz; Jay Stasser; Ninian J. Blackburn; Amina S. Woods; Robert J. Cotter; Christopher D. Incarvito; Arnold L. Rheingold; Kenneth D. Karlin (JBIC Journal of Biological Inorganic Chemistry, 2005)

Sugarcane improvement in Guangxi: Progress and perspectives - Yu-mo Tan; Hong He (Sugar Tech, 2004)

Biodegradation of Dibenzo-p-dioxin, Dibenzofuran, and Chlorodibenzo-p-dioxins by Pseudomonas veronii PH-03 - Hyo-Bong Hong; In-Hyun Nam; Kumarasamy Murugesan; Young-Mo Kim; Yoon-Seok Chang (Biodegradation, 2004)

An optimized gossypol high-performance liquid chromatography assay and its application in evaluation of different gland genotypes of cotton - Yingfan Cai; Hong Zhang; Yu Zeng; Jianchuan Mo; Jinku Bao; Chen Miao; Jie Bai; Fang Yan; Fang Chen (Journal of Biosciences, 2004)

Preparation of a purified, inactivated Japanese encephalitis (JE) virus vaccine in Vero cells - Sun Pyo Hong; Wang-Don Yoo; Robert Putnak; Ashok K. Srivastava; Kenneth H. Eckels; Yong-Ju Chung; Hyune Mo Rho; Soo-Ok Kim (Biotechnology Letters, 2001)